Project Based Learning Model on Elementary School Students' Science Process Skills and Creative Thinking Skills - Amri Apriansyah; Haifaturrahmah; Nursina Sari; Muhammad Nizaar; Siti Alaa (Jurnal Ilmiah Sekolah Dasar, 2024)
Learning that is less innovative through a learning style that is still monotonous by the teacher and learning that only focuses on the cognitive domain will have an impact on learning outcomes, especially science process skills and creative thinking skills. Students become less active in understanding the series of learning activities carried out. This research aims to analyze the effectiveness of the project based learning model on elementary school students' science process skills and creative thinking skills. The research method applied in this study is experimental research using a quasi-experimental type. The sample in this research was 40 students that were divided into two groups. The treatment for the experiment class implements the project based learning model, and the control class uses problem based learning model. The data collection method employed observation, questionnaire, and test techniques. The data analysis technique utilized descriptive statistics and inferential statistics. Research results indicated significant differences in the learning outcomes of the test. The independent sample t-test showed Sig. 2-tailed by 0.016, which means smaller than 0.05 (0.016<0.05). This result shows a significant difference in learning outcomes in which the experiment class is superior to the control class. Later on, the effect of project based learning model on students' science process skills brings significant improvement by 63.7%, and creative thinking skills improves by 9.2 %. The study concludes that the project based learning model is proven effective in improving students' science process skills and creative thinking skills.